On the Staphylinidae of La Gomera (Canary Islands), with descriptions of four new species (Coleoptera). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1999)
The results of a field trip to La Gomera are presented. More than 45 species of Staphylinidae were recorded, at least 31 of them either Canarian endemics or island endemics of La Gomera. Four species, all of them presumably island endemics, are described and distinguished from related taxa: Micropeplus gomerensis sp. n., Leptobium gomerense sp. n., Oligota stefaniae sp. n., and Alevonota sollemnis sp. n. Their sexual characters and further distinguishing characters are figured.KeywordsColeoptera, Staphylinidae, Micropeplus, Leptobium, Oligota, Alevonota, Palaearctic, Canary Islands, La Gomera, taxonomy, new species, endemism.Nomenclatural Actssollemnis Assing, 1999 (Alevonota), spec. n.gomerense Assing, 1999 (Leptobium), spec. n.gomerensis Assing, 1999 (Micropeplus), spec. n.stefaniae Assing, 1999 (Oligota), spec. n.